2003
DOI: 10.2337/diacare.26.4.1079
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Pump Therapy

Abstract: OBJECTIVE -To conduct a meta-analysis of the metabolic and psychosocial impact of continuous subcutaneous insulin infusion (CSII) therapy on adults, adolescents, and children.RESEARCH DESIGN AND METHODS -Studies were identified and data regarding study design, year of publication, sample size, patient's age, diabetes duration, and duration of CSII therapy were collected. Means and SDs for glycohemoglobin, blood glucose, insulin dosages, and body weight for CSII and comparison conditions were subjected to meta-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
316
2
40

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 501 publications
(386 citation statements)
references
References 79 publications
24
316
2
40
Order By: Relevance
“…It should also be noted that the heterogeneity is not so much caused by qualitatively different results, but by quantitative differences. From these limitations it is clear that the results obtained from this meta-analysis have to be interpreted cautiously even though they are consistent with previously published meta-analyses [7,8,47,48].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…It should also be noted that the heterogeneity is not so much caused by qualitatively different results, but by quantitative differences. From these limitations it is clear that the results obtained from this meta-analysis have to be interpreted cautiously even though they are consistent with previously published meta-analyses [7,8,47,48].…”
Section: Discussionsupporting
confidence: 83%
“…Since in many of the included trials the different definitions of hypoglycaemia were susceptible to bias and the endpoint detection was not blinded, results on hypoglycaemic events have to be viewed as inherently uncertain. Like Pickup et al [7], Colquitt et al [47] and Weissberg-Benchell et al [48], we also did not perform a meta-analysis on hypoglycaemic events, due to differences in definitions of hypoglycaemic episodes, the difference in study duration, the small numbers of patients with severe hypoglycaemic episodes and the often missing measures of variance.…”
Section: Discussionmentioning
confidence: 99%
“…The finding that HbA 1c concentrations were greater in adolescents than in younger age groups could reflect greater parental supervision of treatment in young children, as reported in other studies [26]. The finding that a longer duration of CSII use was associated with higher HbA 1c is at variance with a previous meta-analysis [27], which found that patients who received pump therapy for at least 1 year showed significant improvements in glycated haemoglobin, whereas no significant improvement was seen in patients treated for <1 year. Nevertheless the finding that many patients included in the previous survey increased their number of boluses between the previous survey and the present study indicates that constant re-education and motivation can achieve better long-term glycaemic control with CSII.…”
Section: Discussionmentioning
confidence: 48%
“…The deviation (4) where G is the corresponding blood glucose measurement, is the performance measure that is used as the controlled variable (ψ). The controlled variable vector (assuming four segments) is then (5) where k is the current day.…”
Section: Update the Input Parameters Asmentioning
confidence: 99%
“…CSII pumps are becoming the preferred method to deliver insulin, as CSII therapy significantly improves glycemic control [4]. Pumps have the advantage that basal insulin delivery can be set at different rates for distinct segments of the day (e.g., the Paradigm ® pump, Medtronic MiniMed, Inc., Northridge, CA supports up to 48 segments).…”
Section: Introductionmentioning
confidence: 99%